A Perspective on How User-Centered Design Could Improve the Impact of Self-Applied Psychological Interventions in Low- or Middle-Income Countries in Latin America - Dominguez-Rodriguez, Alejandro; De La Rosa-Gómez, Anabel (Frontiers in Digital Health, 2022)
Global technological progress has generated alternatives for psychological assistance, both for the evaluation and for the treatment of different emotional disorders. Evidence suggests that Internet-based treatments are effective for the treatment of anxiety and depression disorders. However, in Latin America online treatments are still scarce compared to developed countries and have the similar problems as developed countries, such as high dropout rate. One possible solution to help decrease the drop-out rate is to design and develop online interventions based on the needs and characteristics of the users. The user centered design (UCD) is a fundamental concept to develop successful online interventions. The objective of this article is to provide a perspective overview on how UCD could improve the impact of self-applied psychological interventions in low- or middle-income countries in Latin America, however this proposal can also be applied in low- and middle-income countries in other regions of the world. The literature on UCD has demonstrated its efficacy when properly applied in online interventions, however it is not common to see how this methodology has been applied in research in online interventions, and regarding Latin America this is even more scarce with a very limited number of articles implementing the principles of UCD.